A synthetic diphosphoinositol phosphate analogue of inositol trisphosphate. Issue 7 (4th June 2018) - Riley, Andrew M.; Unterlass, Judith E.; Konieczny, Vera; Taylor, Colin W.; Helleday, Thomas; Potter, Barry V. L.
Abstract : We describe the synthesis and biological evaluation of 1-PP-Ins(4, 5)P2, the first diphosphate-containing analogue of the intracellular signalling molecule Ins(1, 4, 5)P3 . Abstract : Diphosphoinositol phosphates (PP-InsPs) are inositol phosphates (InsPs) that contain PP (diphosphate) groups. Converting a phosphate group in an InsP into a diphosphate has been reported to enhance affinity for some binding proteins. We synthesised 1-PP-Ins(4, 5)P2, the first diphosphate analogue of the intracellular signalling molecule InsP3, and examined its effects on InsP3 receptors, which are intracellular Ca 2+ channels. 1-PP-Ins(4, 5)P2 was indistinguishable from InsP3 in its ability to bind to and activate type 1 InsP3 receptors, indicating that the diphosphate modification of InsP3 affected neither affinity nor efficacy. Nevertheless, 1-PP-Ins(4, 5)P2 is the most potent 1-phosphate modified analogue of InsP3 yet identified. PP-InsPs are generally hydrolysed by diphosphoinositol polyphosphate phosphohydrolases (DIPPs), but 1-PP-Ins(4, 5)P2 was not readily metabolised by human DIPPs. Differential scanning fluorimetry showed that 1-PP-Ins(4, 5)P2 stabilises DIPP proteins, but to a lesser extent than naturally occurring substrates 1-PP-InsP5 and 5-PP-InsP5 . The non-hydrolysable InsP7 analogues 1-PCP-InsP5 and 5-PCP-InsP5 showed comparable stabilising abilities to their natural counterparts and may therefore be promising substrate analogues for co-crystallisation with DIPPs.